Ten lessons for a post-pandemic world [compact disc, unabridged] - Zakaria, Fareed (Simon & Schuster Audio, 2020)
CNN host and bestselling author Fareed Zakaria examines how the latest unprecedented crisis of the 21st century will impact the world for years to come.